2009
DOI: 10.1128/aac.00601-09
|View full text |Cite
|
Sign up to set email alerts
|

Development of NS3/4A Protease-Based Reporter Assay Suitable for Efficiently Assessing Hepatitis C Virus Infection

Abstract: A cell culture system for the production of hepatitis C virus (HCV) whole virions has greatly accelerated studies of the virus life cycle and the discovery of anti-HCV agents. However, the quantification of the HCV titers in a whole-virus infection/replication system currently relies mostly on reverse transcription-PCR or immunofluorescence assay, which would be cumbersome for high-throughput drug screening. To overcome this problem, this study has generated a novel cell line, Huh7.5-EG(⌬4B5A)SEAP, that carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Several reports, including ours, have demonstrated that this model can overcome the limitations of the HCV replicon system and enable the discovery of compounds that target various stages of the HCV life cycle. [3][4][5][6][7][8] Using the HCV cell culture system, we previously developed a tube-capture-reverse transcription-polymerase chain reaction (RT-PCR) assay for screening HCV inhibitors and identified bisindolylmaleimides and indolocarbazoles as inhibitors of HCV replication. 4) Here, we describe another screening method for the detection of anti-HCV activity.…”
mentioning
confidence: 99%
“…Several reports, including ours, have demonstrated that this model can overcome the limitations of the HCV replicon system and enable the discovery of compounds that target various stages of the HCV life cycle. [3][4][5][6][7][8] Using the HCV cell culture system, we previously developed a tube-capture-reverse transcription-polymerase chain reaction (RT-PCR) assay for screening HCV inhibitors and identified bisindolylmaleimides and indolocarbazoles as inhibitors of HCV replication. 4) Here, we describe another screening method for the detection of anti-HCV activity.…”
mentioning
confidence: 99%
“…Several recent reports describe systems that can in principle screen for inhibitors targeting different steps of the HCV life cycle via the prevention of the spread of cell culture-derived hepatitis C virus (HCVcc) infection in a cell monolayer (8)(9)(10)(11). Very recently, one such screen based on a colorimetric readout following immunostaining with an anti-E2 antibody identified inhibitors of multiple stages of the HCV life cycle (12).…”
mentioning
confidence: 99%
“…Pan et. al., while developing their similar dual reporter cell line Huh-7.5/EG(D4B5A)SEAP [19], checked various cleavable peptides as well, including the 4A/ 4B signal sequence utilized in this study. In an EGFP-SEAP configuration, the 4A/4B cleavage site appeared to be inaccessible by the viral protease.…”
Section: Discussionmentioning
confidence: 99%
“…Iro et al [18], created a Huh7 cell line (designated Huh7-J20) expressing the identical cassette for rapid and sensitive quantification of HCV infection in cell culture by JFH-1 or JFH-1 chimeric viruses. Finally, Pan et al et al [19], generated a similar stable cell line (designated Huh7.5-EG(D4B5A)SEAP), which is based on the Huh-7.5 cells and the NS4B-NS5A junction region as a recognition sequence for the viral protease .…”
Section: Introductionmentioning
confidence: 99%